Integrated Assessment of Heavy Metal Contamination in Sediments from Gebeng Industrial Estate, Pahang, Malaysia - Md Abdus, Sobahan; Islam, Mir Sujaul (International Science Congress Association, 2015)
Gebeng is one of the most important industrial regions in Pahang, Malaysia. The study was conducted in the Gebeng industrial estate to investigate the effect of industrialization on heavy metal pollution in the surface sediments of the industrial area. In this study, it has been found that the sediments were highly contaminated especially by Co , Hg and As which is supported by the values of enrichment factors, contamination factors, geo-accumulation index, pollution load indexes and contamination assessment by sediment quality guidelines. According to the hierarchical cluster analysis (HCA) the studied heavy metal pollution were ranked as Co> Hg> As> Pb> Zn> Cu> Cr> Cd> Ni>Ba and the sampling stations were ranked as WS1>DSRS3>DSRS1>USRS4>DSRS2>USRS3>WS3>WS2>USRS2>USRS1.Moreover, it was found that all the three zones (the wetland sediments, upstream river sediment and downstream river sediments) were polluted by heavy metals. Three principal components were extracted from principal component analysis, they accounted for more than 84% of the total variability and detected the industrial activities was the source of pollution. The results indicated that the industrial dumping is going on indiscriminately. The study will help in the strategic management of the industries through providing heavy metals pollution of sediments.